Watershed response on rainfall variability using a physical model - Aventurado, Hannah Grace S.; Dizon, Cornelio Q. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
This study aims to determine the influence of rainfall variability on generated surface runoff with the use of a physical model. Three storm properties were experimented on: a) spatial variability, b) temporal variability and c) direction of storm movement. Rainfall simulations were performed with the physical hydrologic model, S12 MKil Hydrology System, manufactured by Armfield. Centroidal distance of the storm has not significantly affected the peak flow of the generated runoff, although storms with cores closer to the outlet yielded a greater volume of runoff than rainfall occurring far from the outlet. Areal coverage of rainfall had a more noteworthy contribution to the peak discharge. As the coverage of area of rainfall increases, so does the peak flow of the generated runoff. An increasing temporal pattern was observed to produce runoff with a higher peak flow than that of a decreasing temporal pattern. Both varying intensity patterns were expected to yield a higher peak discharge than rainfall of constant intensity, however the results of the simulations had only the increasing temporal pattern prove this right. As for the experiments on the direction of rainfall movement, rainfall moving upstream had an earlier rise but a lower peak flow than rainfall moving downstream. As expected, storm moving along the direction of stream flow would produce a higher peak. Through these simulations, accounting for rainfall variability in modeling was emphasized as it has significantly impacted runoff even in a watershed of a smaller scale.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Watershed hydrology; Hydrologic models